Strategi Pembelajaran Langsung (Direct Instruction) - Nayla Nada Asyva; Jum’atul Hasanah; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the Direct Instruction strategy, a teacher-centered learning approach that emphasizes systematic and structured delivery of material. The purpose of this study is to address the following research questions: (1) What is meant by direct instruction strategy? (2) What are the characteristics of the direct instruction strategy? (3) What are its strengths and weaknesses? and (4) How is the direct instruction strategy applied in Islamic Religious Education (PAI) subjects? This article uses a library research method by examining various relevant theoretical sources. The findings indicate that direct instruction is an effective approach for delivering factual and procedural knowledge, particularly when learning objectives focus on mastering basic skills and understanding concepts in stages. This strategy is characterized by clear teacher guidance, structured learning steps, and continuous assessment. Its advantages include time efficiency and ease of classroom control, while its drawbacks involve limited student participation and less development of critical thinking skills. In the context of PAI learning, this strategy can be effectively applied to memorization materials, basic conceptual understanding, and character formation through concrete examples and teacher modeling.